A key gene, violaxanthin de-epoxidase-like 1, enhances fucoxanthin accumulation in Phaeodactylum tricornutum - Chenjie Li; Yufang Pan; Wenxiu Yin; Jin Liu; Hanhua Hu (Biotechnology for Biofuels and Bioproducts, 2024)
Abstract Background Fucoxanthin has been widely investigated owing to its beneficial biological properties, and the model diatom Phaeodactylum tricornutum, possessing fucoxanthin (Fux) chlorophyll proteins as light-harvesting systems, is considered to have the potential to become a commercial cell factory for the pigment production. Results Here, we compared the pigment contents in 10 different P. tricornutum strains from the globe, and found that strain CCMP631 (Pt6) exhibited the highest Fux content but with a low biomass. Comparison of mRNA levels revealed that higher Fux content in Pt6 was related with the higher expression of gene violaxanthin de-epoxidase-like (VDL) protein 1 (VDL1), which encodes the enzyme catalyzing the tautomerization of violaxanthin to neoxanthin in Fux biosynthesis pathway. Single nucleotide variants of VDL1 gene and allele-specific expression in strains Pt1 (the whole genome sequenced strain CCMP632) and Pt6 were analyzed, and overexpressing of each of the 4 VDL1 alleles, two from Pt1 and two from Pt6, in strain Pt1 leads to an increase in downstream product diadinoxanthin and channels the pigments towards Fux biosynthesis. All the 8 VDL1 overexpression (OE) lines showed significant increases by 8.2 to 41.7% in Fux content without compromising growth, and VDL1 Allele 2 OE lines even exhibited the higher cell density on day 8, with an increase by 24.2–28.7% in two Pt1VDL1-allele 2 OE lines and 7.1–11.1% in two Pt6VDL1-allele 2 OE lines, respectively. Conclusions The results reveal VDL1, localized in the plastid stroma, plays a key role in Fux over-accumulation in P. tricornutum. Overexpressing VDL1, especially allele 2, improved both the Fux content and growth rate, which provides a new strategy for the manipulation of Fux production in the future.